Scanning electron microscopy of acantholysis in pemphigus foliaceus Microscopia eletrônica de varredura da acantólise no pênfigo foliáceo - Hiram Larangeira de Almeida Jr; Aline Hatzenberger Leitão; Gabriela Rossi; Nara Moreira Rocha; Ricardo Marques e Silva (Sociedade Brasileira de Dermatologia, 2013)
We performed scanning electron microscopy of an inverted blister roof in a case of pemphigus foliaceus. The loss of intercellular adherence could be easily seen with low magnification. The acantholytic keratinocytes displayed an irregular and sometimes polygonal contour. Round cells, typically seen in light microscopy, were also observed. The examination of a blister roof allows ultrastructural documentation of the acantholytic changes. Realizamos microscopia eletrônica de varredura do teto invertido de uma bolha de um caso de pênfigo foliáceo. Com pequeno aumento, a perda da adesão intercelular pôde ser vista claramente. Os queratinócitos acantolíticos demostraram um contorno irregular, algumas vezes poligonal. Células arredondadas, como vistas tipicamente na microscopia óptica, também foram observadas. O exame de um teto de bolha permite uma documentação ultraestrutural das alterações acantolíticas.